ASPEK PRO ENVIRONMENTAL BEHAVIOR DALAM PILIHAN KONSUMEN UNTUK MENGGUNAKAN KANTONG PLASTIK - Saraswaty, Amrita Nugraheni (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
This research was conducted with the background of the fact of environmental problems caused by maladaptive human behavior. Especially the indifference and misunderstanding of most urban people against environmental rules leads to a decline in urban environmental quality. In City of Denpasar and Badung, various community activities cause environmental degradation. This study aims to determine aspects of pro-environment behavior of urban communities in the city of Denpasar and Badung mainly the consumer's decision to use a plastic bag. To achieve this goal, this research is done by quantitative approach with respondents of urban city community in Denpasar and Badung. In-depth interviews will be conducted on the research sample. From the analysis results it can be concluded that 1) respondents with age range 13-54 years have a more diverse way in channeling pro environmental attitude than the older respondents, and 2) most respondents have sufficient knowledge about cleanliness and environmental conservation, but the action of the use of plastic bags made so far is still based on economic considerations and carried by the pattern of behavior of closest people (family) and the surrounding community. Keywords : pro environmental behavior, urban community, Denpasar city, sustainable development, green behavior